PTU-092 Patient And Professionals Perceptions Of Travel Behaviour In Inflammatory Bowel Disease. (9th June 2014) - Mulligan, J-P; Greveson, K; Shepherd, T; Hamilton, M; Murray, CD
Abstract : Introduction: Travellers with inflammatory bowel disease (IBD) are at greater risk of travel-related morbidity. 1 ECCO recommend patients seek expert advice prior to travel, including information on vaccination and obtaining antibiotics for self-treatment of travellers diarrhoea. 2 Wasan et al. report only 3.5% of patients on immunosuppression therapy were counselled on avoiding particular live vaccines 3 and 30% of gastroenterologists would erroneously recommend live vaccines. 4 Methods: We explored both patient and gastroenterology health care professionals (HCP) perceptions of IBD and travel: whether disease affected travel, interventions people took to travel, and whether ECCO guidelines were being followed. IBD patients attending our IBD clinic during November 2013 were asked to complete a questionnaire collecting demographic, disease specific and travel related information. Using N-ECCO and RCN IBD nurse network databases, HCP were asked to complete online questionnaire collecting information on perceptions of IBD and travel, confidence at providing travel advice, and the content of that advice. Results: 136 IBD patients (67[49%] Crohn's disease, 60[44%] male, median age 38 years[range 18–85]) and 105 HCP (98/105[93%] nurse specialists, 6/105[6%] consultant, 1/105[1%] registrar) responded. 85%[106/136] patients report feeling adequately prepared for travel, although only 24%[32/136] seek travel medical advice of any kind and only 11%[15/136] from the IBD team; all despite 60%[82/136] reporting their IBD affected travel. Despite recommendations, only 4%[5/136] had been prescribed antibiotics for self-medication of travellers diarrhoea. 52%[36/69] of immunosuppressed patients are unaware they should avoid live vaccines. 39%[53/136] patients buy travel insurance covering IBD, 70%[37/53] of which pay a premium. 70%[74/105] HCP felt IBD might limit travel in patients. 70%[74/105] HCP are confident giving travel advice, but 51%[38/74] refer them to a travel clinic. 90%[94/105] are confident giving advice on travellers diarrhoea, but only 54%[57/105] on vaccinations and 40%[42/105] on insurance. Conclusion: Patients travel is affected by IBD, however, few seek expert medical advice prior to travel. HCP agree IBD affects travel and a majority are confident giving limited advice. It is concerning 52% of immunosuppressed patients are unaware they should avoid live vaccines, and only 54% of HCP are confident giving advice on vaccinations. Results support the need for further travel specific research and better education in both groups. References: Soonwala et al . Inflamm Bowel Dis 2012;18(11):2079–85 Rahier et al . Journal of Crohn's and Colitis 2009;3(2):47–91 Wasan et al . Inflamm Bowel Dis 2014;20(2):246–50 Wasan et al . Inflamm Bowel Dis 2011;17(12):2536–60 Disclosure of Interest: None Declared.